Renewal and Transformation of Cultures in Modern World: a case study of cultural change during Mustafa Kemal Ataturk - Balauch, Farzana; Rasheed Khan , Abdul (SADIQ Journal of Pakistan Studies, 2022)
As a result of globalization, cultural patterns and trends are increasingly being embraced all over the world. Culture in the modern world has shifted from being a set of practices to more of a philosophy. It is not a new practice, but throughout the early nineteenth century, it became more widespread for powerful states to acquire the cultures of other influential nations. To fully grasp this theory of cultural change and cultural adoption, it is necessary to first have some familiarity with Ataturk and the reforms he enacted, as well as the concept of cultural transformation. These different kinds of adoption had an effect on various parts of cultural life, but this sort of nationalism was also a product of the revolution that brought about these changes. This article makes an attempt to trace the transformation of culture and society under the leadership of Mustafa Kemal Ataturk. This includes the language, clothing, education system, and religious practices. However, the author restricts the authority of Turks to the geographical boundaries that exist at the present time. The goal of this endeavour was to bring the Turks and Turkish culture up to date by modelling it after that of the West, which at the time was the most powerful region in the world in all respects. The foundation had been laid for the achievement of this agenda; nevertheless, if these reforms were not implemented, all of these reforms were regarded as vital in order to accept modern norms and values. These cultural shifts, along with the political shifts that accompanied them, were embraced as part of a revolutionary movement. This article delves into all of these current tendencies, as well as Ataturk's ability to make profound changes in Turkish society in a relatively short amount of time when he was in power.